Creating Target Publics for Welfare Policies A Comparative and Multi-level Approach (Logic, Argumentation & Reasoning, Interdisciplinary Perspectives from the Humanities and Social Sciences,, 2018)
This volume analyzes welfare policies by looking at the making of their target publics. It examines how these populations are identified and constructed by policy making. The contributors apply the classic theoretical question about who gets what, when, and how, but also suggest the revisiting of policy-feedback analysis. Coverage includes empirical case studies in different geographical areas. It looks at Europe, the United States and also considers Mayotte, set in a post-colonial context. The chapters also examine different aspects of welfare, including the bureaucratic treatment of marginalized populations as well as the middle class. The authors draw on diverse conceptual approaches and investigative methodologies. They conduct participant observation in public or nonprofit organizations, explore administrative records, and interview actors at various stages of policymaking. This qualitative material is then combined with relevant quantitative data. Readers are guided through a multilevel approach of welfare policies, from their definition to their implementation. They gain insight into the targeting of publics, from the higher reaches of government to the most underprivileged groups of the social world. Overall, the book compares different national contexts and social policy fields. This approach unearths regularities, enabling the authors to reassess major contemporary transformations of the welfare State.